A role of peripheral myelin protein 2 in lipid homeostasis of myelinating schwann cells. Issue 9 (21st May 2014) - Zenker, Jennifer; Stettner, Mark; Ruskamo, Salla; Domènech‐Estévez, Enric; Baloui, Hasna; Médard, Jean‐Jacques; Verheijen, Mark H. G.; Brouwers, Jos F.; Kursula, Petri; Kieseier, Bernd C.; Chrast, Roman
<x xml:space="preserve">Abstract</x> Peripheral myelin protein 2 (Pmp2, P2 or Fabp8), a member of the fatty acid binding protein family, was originally described together with myelin basic protein (Mbp or P1) and myelin protein zero (Mpz or P0) as one of the most abundant myelin proteins in the peripheral nervous system (PNS). Although Pmp2 is predominantly expressed in myelinated Schwann cells, its role in glia is currently unknown. To study its function in PNS biology, we have generated a complete Pmp2 knockout mouse (Pmp2‐/‐). Comprehensive characterization of Pmp2‐/‐ mice revealed a temporary reduction in their motor nerve conduction velocity (MNCV). While this change was not accompanied by any defects in general myelin structure, we detected transitory alterations in the myelin lipid profile of Pmp2‐/‐ mice. It was previously proposed that Pmp2 and Mbp have comparable functions in the PNS suggesting that the presence of Mbp can partially mask the Pmp2‐/‐ phenotype. Indeed, we found that Mbp lacking Shi‐/‐ mice, similar to Pmp2‐/‐ animals, have preserved myelin structure and reduced MNCV, but this phenotype was not aggravated in Pmp2‐/‐/Shi‐/‐ mutants indicating that Pmp2 and Mbp do not substitute each other's functions in the PNS. These data, together with our observation that Pmp2 binds and transports fatty acids to membranes, uncover a role for Pmp2 in lipid homeostasis of myelinating Schwann cells. GLIA 2014;62:1502–1512